1975
DOI: 10.1111/j.1939-0025.1975.tb01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher ratings of children vulnerable to psychopathology.

Abstract: Teacher behavior ratings were collected on children of schizophrenic, depressed, and normal mothers. Children of schizophrenic and depressed mothers were rated higher than were children of normal mothers on classroom disturbance, impatience, disrespect‐defiance, and inattentiveness‐withdrawal; they were rated lower on comprehension, creative initiative, and relatedness to teacher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
17
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 14 publications
(1 reference statement)
3
17
0
Order By: Relevance
“…In addition, depression may effect overall ability of the mother to parent the child in a more pervasive way than does schizophrenia which may show in only certain aspects of parenting. These findings are supported by the work of Weintraub, Neale, and Liebert [10] who found that teachers rated the classroom behavior of children of depressed and schizophrenic women as deviant and in rather similar ways.…”
supporting
confidence: 73%
“…In addition, depression may effect overall ability of the mother to parent the child in a more pervasive way than does schizophrenia which may show in only certain aspects of parenting. These findings are supported by the work of Weintraub, Neale, and Liebert [10] who found that teachers rated the classroom behavior of children of depressed and schizophrenic women as deviant and in rather similar ways.…”
supporting
confidence: 73%
“…Teachers have been shown to make accurate judgments regarding extremely disparate group of students (Nelson, 1971;Greenwood et al, 1975) as well as accurate specific judgments about less disparate groups of children such as those found in a traditional classroom setting (Bolstad and Johnson, 1977). In addition, research supports teacher ratings as an effective means of selecting potentially emotionally disabled students (Bolstad and Johnson, 1977;Bower, 1969;Weintraub et al, 1975). Teacher ratings have been validated against behavioral observations as well as sociometric data (Bolstad and Johnson, 1977;Greenwood et al, 1977;Pekarik et al, 1976).…”
Section: Introductionmentioning
confidence: 94%
“…This rationale has been criticized by some (Hanson, Gottesman, and Heston, 1976;Weintraub, Neale, and Liebert, 1975) Teacher ratings also failed to differentiate between the two diagnostic groups, whereas they did distinguish the latter groups from the controls. Boys were rated more deviant than girls, although the authors did not specify which behaviors the teachers felt were deviant.…”
mentioning
confidence: 99%
“…Peers judged their classmates using a modified version of the Bower Class Play (Bower, 1969 Weintraub and his colleagues (Weintraub, Neale, and Liebert, 1975;Weintraub, Prinz, and Neale, 1978) also used teacher and peer ratings to evaluate behaviors of children of schizophrenic and depressed mothers. Controls were chosen in the same manner as Role (1972).…”
mentioning
confidence: 99%